2005
DOI: 10.1590/s0036-46652005000600005
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of two karyotypic forms of Anopheles aconitus (Diptera: Culicidae) to Plasmodium falciparum and P. vivax

Abstract: Four laboratory-raised colonies of two karyotypic forms of Anopheles aconitus, i.e., Form B (Chiang Mai and Phet Buri strains) and C (Chiang Mai and Mae Hong Son strains), were experimentally infected with Plasmodium falciparum and P. vivax using an artificial membrane feeding technique and dissected eight and 12 days after feeding for oocyst and sporozoite rates, respectively. The results revealed that An. aconitus Form B and C were susceptible to P. falciparum and P. vivax, i.e., Form B (Chiang Mai and Phet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…sinensis was collected from Mae Tang District, Chiang Mai Province, Thailand. Anopheles cracens was in a free-mating colony established for more than two decades in the insectariums of the Department of Parasitology, Chiang Mai University, Thailand and was used as a control, since it is known to be highly susceptible to P. vivax [ 22 ]. These colonies were reared using the method described by Park et al [ 23 ] in an insectary room at 27 ± 2°C, 70–80% relative humidity with 12:12 hr light and dark photoperiods adjusted by fluorescent lighting.…”
Section: Methodsmentioning
confidence: 99%
“…sinensis was collected from Mae Tang District, Chiang Mai Province, Thailand. Anopheles cracens was in a free-mating colony established for more than two decades in the insectariums of the Department of Parasitology, Chiang Mai University, Thailand and was used as a control, since it is known to be highly susceptible to P. vivax [ 22 ]. These colonies were reared using the method described by Park et al [ 23 ] in an insectary room at 27 ± 2°C, 70–80% relative humidity with 12:12 hr light and dark photoperiods adjusted by fluorescent lighting.…”
Section: Methodsmentioning
confidence: 99%
“…aconitus forms B and C were susceptible to P. vivax and P. falciparum, and that An. aconitus form C was susceptible only to P. vivax (Junkum et al, 2005). …”
Section: Asia and Asia-pacificmentioning
confidence: 97%
“…dirus for P. vivax has been estimated (Prakash et al, 2001). Experimental infection from humans (Wirtz et al, 1985), monkeys (Collins et al, 2009) and membrane feeding has been shown (Coleman et al, 2004;Junkum et al, 2005). …”
Section: An Dirus Complex Yesmentioning
confidence: 99%
“…Besides being recently established as the main vector for P. knowlesi in Kuala Lipis , An. cracens has also been proven to be an efficient laboratory vector for both P. falciparum and P. vivax [5,8]. Upon comparing filarial vector competence between An.…”
Section: Introductionmentioning
confidence: 99%